Functions of Consciousness: the Problem of Classification - Акімова, Наталія Володимирівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2020)
The "complex problem of consciousness" in its functional aspect is analyzed in the article. The purpose of the article is to structure ideas about the functions of consciousness, to reconcile them, to propose an appropriate classification. To achieve this goal, the following methods and techniques were used: a) deduction; c) analysis; d) synthesis; e) generalization; e) systematization; e) modeling. So the analysis of the popular classification of consciousness functions in psychological literature was represented. Particularly there are the classification of K.G. Jung; L.S. Vygotsky, S.L. Rubinstein, B.G. Ananiev, O.M. Leontiev, O. R. Luria, V.P. Zinchenko, O.V. Petrovsky, R.S.Nemov, G.V. Akopov, O.A. Istomina and V.V. Pavlovsky, O. Skripchenko, L. Dolynska, O. Sergeenkova, O. Stolyarchuk, O. Kokhanova and O. Paseka; O.A. Gulbs, N.F. Shevchenko, A.G. Samoilova). The classifications of consciousness functions in related humanities (philosophy and linguistics) are given for comparison. In general, more than twenty classifications of consciousness functions have been analyzed. The review highlights their advantages and disadvantages. It is concluded that to solve the "complex problem of consciousness" requires first of all well-established communication between scientists, constructive criticism, a well-founded theoretical approach based on generally accepted ideas that have become axioms in psychology. Therefore, on the basis of the analyzed classifications, the author’s understanding of the problem is proposed. Consciousness is a level of the psyche that contains evaluations, attitudes and ideals about the world and oneself. The main function of consciousness is reflection (subjective reflection of the objective world), that interact with other components of the psyche and realize by a number of specific functions: empirical ( consciousness + perception and consciousness + memory), orientation (consciousness + attention), prognostic (consciousness + thinking), evaluative (consciousness + emotions), psychosomatic (consciousness + body), meaning-making (consciousness + speech) and regulation of behavior (consciousness + will).